Advances in grinding technology in China with application in steel roller manufacturing. (January 2022) - Wang, Liping; Wang, Dong; Cao, Yuzhong; Chen, Zhanying; Zhang, Pengxiang; Zhang, Yun; Li, Xuekun
Grinding of large or ultralarge components to achieve stringent quality is always challenging in China's manufacturing industry, for example, roller for steel strip production. Compared with transverse cylindrical grinding, roller grinding requires high-precision multiaxis motion. In addition, with the increasing demand for process efficiency, the in-process measurement and process compensation become necessary for higher process reliability and productivity. This article presents the state-of-the-art and emerging technology in China's roller grinding, which includes heavy-duty grinding machine optimization, high-performance tooling design, in-process geometrical accuracy compensation, in-site machine vision for gloss defect, and intelligent process parameter optimization strategy. Therefore, this article will shed light on the development trend of the enabling technology toward intelligent roller grinding with higher accuracy, dexterity, and efficiency.